Design and synthesis of PID controller based on fuzzy - Islam, Md. Shabiul; Amin, Nowshad; Uz-Zaman, A.S. M. Mukter; Bhuyan, Mohammad Shaharia (2007)
This paper describes the hardware implementation of a PID-type (Proportional- Integral - Derivative) Fuzzy Logic Controller (FLC) algorithm using VHDL to use in transportation cruising system. The cruising system has developed to avoid the collisions between vehicles on the road. The PID-type FLC provides a reference for a car to either increase or decrease the speed of the vehicle depending on the distance of the preceding vehicle when it gets too close or alert the driver when necessary. The PID-type Fuzzy Controller algorithm is first developed using Matlab platform. The Mamdani Fuzzy Inference is studied and applied to design the PID-type Fuzzy controller hardware system. The controller system then is implemented using VHDL. The synthesis tool, Quartus II is used to synthesize the VHDL codes to obtain the Register Transfer Level (RTL) view of the FLC hardware. The motivation in designing is the Fuzzy based PID cruising controller is cheaper controller in cost compare to conventional PID controller system and thus make it available to the entry-level vehicles such as the national car. This can be further reduced the road accident and ensure the safety of the road users in the future.